Faktor-Faktor yang Memengaruhi Terjadinnya Dismenore Primer pada Remaja Putri - Nazhifan Zalfaa Sujatmiko Putri; Apriliani Yulianti Wuriningsih; Tutik Rahayu (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
There is a substantial increase in physical, psychological, and emotional development during adolescence, the developmental period before adulthood. Primary dysmenorrhea, or menstrual pain caused by an unexplained medical cause, affects many young women during this period and can negatively impact their learning ability and overall well-being. This study aims to analyze the factors influencing the occurrence of primary dysmenorrhea in adolescent girls at SMA Negeri 10 Semarang. This study used a cross-sectional technique to measure correlation. A questionnaire was used to collect data. Using a stratified random sampling procedure, a total of 128 respondents were selected. Multiple logistic regression and the chi-square test were used for statistical analysis of the collected data. Based on the analysis results obtained from 128 research respondents, it was shown that the duration of menstruation (p=0.003), family history (p=0.000), body mass index (p=0.003), and physical activity (p=0.003) were significantly associated with the occurrence of primary dysmenorrhea. Meanwhile, age at menarche (p=0.060), and menstrual cycle (p=0.654) did not show a significant relationship. Conclusion there are factors that influence the occurrence of primary dysmenorrhea in female adolescents at SMA Negeri 10 Semarang.